Polske tvangsarbeidere i Norge i krigsärene - fra registreringen til repatrieringen - Denkiewicz-Szczepaniak, Emilia (Folia Scandinavica Posnaniensia, 2007)
Most of the compulsory foreign workers in Norway during the Second World War were employed by the Organization Todt, a paramilitary construction company from The Third Reich, named after its founder, engineer Fritz Todt. This organization received the greatest number o f construction tasks in Norway, including permanent fortifications. Polish workforce from territories incorporated into the Third Reich and from General Gouvernement were sent to Norway as compulsory workforce o f this organization. Poles in Norway represented the largest group among all foreigners. They were transferred to different places around Norway, but most o f them in the area north of the Arctic Circle. This article focuses on their stay in Norway during the Second World War - from their registration until repatriation.